Cranial ultrasound assessment of gestational age in low birthweight infants. Issue 4 (April 1989) - Murphy, N P; Rennie, J; Cooke, R W
Abstract : The anatomical features of the cerebral hemispheres of 97 infants were studied by ultrasonography. A scoring system was devised based on anatomical and ultrasound appearances and compared with gestational age calculated from the date of the mother's last period. There was a significant positive correlation between gestational age and ultrasound score. Cranial ultrasonography is an accurate and reproducible method of assessing gestational age in low birthweight infants.